2019
DOI: 10.1371/journal.pone.0212508
|View full text |Cite
|
Sign up to set email alerts
|

Do open educational resources improve student learning? Implications of the access hypothesis

Abstract: Open Educational Resources (OER) have been lauded for their ability to reduce student costs and improve equity in higher education. Research examining whether OER provides learning benefits have produced mixed results, with most studies showing null effects. We argue that the common methods used to examine OER efficacy are unlikely to detect positive effects based on predictions of the access hypothesis. The access hypothesis states that OER benefits learning by providing access to critical course materials, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 28 publications
0
43
1
Order By: Relevance
“…Many proponents of OER adhere to the "access hypothesis, " which refers to the idea that OER improve performance because more students are able to access the textbook (Grimaldi et al, 2019). Contrary to this hypothesis, we failed to detect differences in the percentage of students who reported using the open vs. commercial textbooks or in the final course outcomes of these two groups.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Many proponents of OER adhere to the "access hypothesis, " which refers to the idea that OER improve performance because more students are able to access the textbook (Grimaldi et al, 2019). Contrary to this hypothesis, we failed to detect differences in the percentage of students who reported using the open vs. commercial textbooks or in the final course outcomes of these two groups.…”
Section: Discussioncontrasting
confidence: 92%
“…If it is accepted that a core problem addressed by OER is access to textbooks for those who are otherwise unable to afford them, it is also logical that OER would predominantly benefit those students unable to purchase a commercial textbook. Grimaldi et al (2019) conducted a set of simulation studies to examine this issue. They found that, in a study of 10,000 students where 80% of students could access the book, there was only a 56.5% chance that the null hypotheses (no effect of OER on performance) would be successfully rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue when considering findings on open textbook adoption is the access hypothesis, which articulates that students have improved access to open textbooks compared to commercial textbooks because there is no cost barrier (Grimaldi et al, 2019). Based on the access hypothesis, open textbooks would primarily benefit students who could not afford commercial textbooks because they would not struggle academically from a lack of materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students who can afford commercial textbooks would not have an academic advantage in courses with open textbooks because these students would have the textbook regardless of whether instructors adopted commercial or open textbooks. According to Grimaldi et al (2019), the overall lack of differences in student learning outcomes when open textbooks are adopted may be due to the small number of students who benefit from the access open textbooks afford.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fortunately, there are a number of other benefits to engaging in OE initiatives, apart from financial gains. By offering OER as learning materials to students who do not have access to commercial textbooks, their study results improve (Jhangiani, Dastur, Le Grand, & Penner, 2018), a concept that is called the access hypothesis (Grimaldi, Basu Mallick, Waters, & Baraniuk, 2019). Survey results show that working with OER benefits educators as well, because it helps them to learn about new topics and to develop new ideas for teaching (Weller, de los Arcos, Farrow, Pitt, & McAndrew, 2015).…”
Section: Introductionmentioning
confidence: 99%